Embracing successful ICT integration through MIC transformational model: examplary prectices of a Malaysian school leader - Yusuf, Byabazaire; Sailin, Siti Nazuar; Mohamed, Abdul Halim (IGI Global - All Rights Reserved, 2019)
The current worldwide ICT and digital transformation requires new leadership to demonstrate knowledge and skills suitable for the digital age. As ICT development advances, school leaders should maximize ICT usage in classrooms. This chapter highlights exemplary leadership practices by a Malaysian primary school leader. The objectives of the research are (1) to document leadership styles in managing teachers to successfully integrate ICT in their classrooms and (2) to investigate leadership strategies for successful ICT integration. A case study approach involving a semi-structured interview, observations, and documentary analysis were used. The data revealed that the leader pursued an innovative approach to instill technological transformation. Teachers acquired appropriate ICT skills essential to perform their tasks. The study reveals that successful ICT integration was achieved through the application of Maintain ➧Improve ➧ Change (MIC) as part of transformational model practices based on the vision of the Ministry of Education and other strategies discussed in the chapter.